Sebaran Pohon Namnam (Cynometra cauliflora L.) Di Pulau Sangihe Besar, Kabupaten Kepulauan Sangihe, Provinsi Sulawesi Utara. - mananohase, maurend claudya; Lasut, Marthen T.; Langi, Martina A. (Silvarum, 2023)
This study aims to determine the distribution of the namnam tree (Cynometra cauliflora L.) on Sangihe Besar Island, Sangihe Archipelago District, North Sulawesi Province. The research was carried out from December 2022 to January 2023. The initial research was carried out by conducting an initial survey at the research location, the initial survey was carried out to find out information and the location of the Namnam tree. The variables observed in this study were the habitat or growing location, the altitude where it grew, and the coordinates of the growing location. In this research, namnam trees were found totaling 30 trees with different coordinate points, with the greatest distribution occurring in the lowlands.